2019
DOI: 10.1038/s41598-018-38396-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio as predictors of clinical outcome in patients with gallbladder cancer

Abstract: Some inflammatory biomarkers are associated with the post-surgical prognosis in cancer patients. However, their clinical importance in gallbladder cancer has rarely been explored. The aim of this study is to assess the efficacy of surgical intervention and the effectiveness of preoperative test on neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and monocyte-to-lymphocyte ratio (MLR) for predicting the prognosis in gallbladder cancer patients. In this study, a total of 255 gallbladder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Platelet to lymphocyte ratio, a systematic inflammatory maker, was initially used in clinical practice to predict the prognosis of oncologic disorders. 27,28 Recently, this marker has been used as a prognostic marker in cardiovascular diseases, such as ACS, CAD, atrial fibrillation, and heart failure. 10,20,[29][30][31] Kurtul and Ornek assessed clinical trials to evaluate the association between PLR and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet to lymphocyte ratio, a systematic inflammatory maker, was initially used in clinical practice to predict the prognosis of oncologic disorders. 27,28 Recently, this marker has been used as a prognostic marker in cardiovascular diseases, such as ACS, CAD, atrial fibrillation, and heart failure. 10,20,[29][30][31] Kurtul and Ornek assessed clinical trials to evaluate the association between PLR and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the only potentially curative treatment for GB cancer, but even after complete resection, locoregional and/or distant recurrences frequently become main problems 16 . Conceptually, additional adjuvant treatment modalities, such as chemoradiotherapy (CRT) and chemotherapy (CTx), are required to decrease both locoregional and distant recurrences and subsequently improve survival in patients with GB cancer undergoing surgical resection 5,723 . However, the role of adjuvant treatments and optimal treatment modalities remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, inflammatory biomarkers are associated with postoperative prognosis of patients with gallbladder cancer. Additionally, it has been reported that an increase in the ratio of neutrophils versus lymphocytes before surgery is related to shortened overall survival of gallbladder cancer patients [ 20 ]. The specific mechanism of UDCA in reducing leukocyte content is not clear.…”
Section: Discussionmentioning
confidence: 99%